Non-fragile asynchronous reliable sampled-data control for uncertain fuzzy systems with Bernoulli distribution. Issue 6 (April 2020) - Luo, Jinnan; Tian, Wenhong; Zhong, Shouming; Shi, Kaibo; Liao, Daixi
Abstract: In this study, the non-fragile asynchronous reliable sampled-data control for uncertain Takagi–Sugeno fuzzy systems with Bernoulli distribution is addressed. The system involves both the randomly occurring uncertainties of parameters in the fuzzy system model and randomly occurring gain perturbations of the controller. By introducing three stochastic variables, a new model structure satisfying Bernoulli distribution is formulated to describe the system and the controller. The main purpose of this study is to design the non-fragile asynchronous reliable sampled-data controller such that the considered system is finite-time bounded and possesses finite-time mixed H ∞ and passive performance. Based on an improved Lyapunov–Krasovskii functional, newly bounding inequalities and stochastic processing method, new conditions satisfying the required result are derived for the uncertain fuzzy systems in terms of linear matrix inequalities. Moreover, a modified non-fragile asynchronous reliable sampled-data controller is designed. Finally, two numerical examples are given to demonstrate the effectiveness of the presented results.